Such painful knowledge: hope and the (un)making of futures in Cape Town - Cupido, Shannon (School of African and GenderStuds, Anth and Ling, 2021)
Recent writing in the anthropology of affect and cognate fields has positioned hope as a useful category with which to examine socio-political life and formulate a political and theoretical response adequate to its form. This dissertation extends this endeavour by exploring the ‘hopeful projects' mothers and families undertake in order to secure their children's futures in contemporary Cape Town. Based on ethnographic research conducted with Black mothers between March and October 2018, I argue that the supposedly private maternal hopes my interlocutors hold are in fact indexical of the ways in which social inequality functions and becomes manifest in everyday life and care. Situated at the interface of embodied experience and political histories, their hopes are indicative of how liberal logics of selfextension, self-mastery, and self-maximisation are inhabited to produce alternative futures. At the same time, however, such hopes are continually undone by contexts of intractable structural violence and deprivation, reinvested into normative notions of kinship, domesticity, sexuality, and the body, or marshalled to perform reparative work that should properly fall under the purview of the state. In detailing the ways in which my interlocutors attempt to craft more capacious, more just, and more materially abundant futures for their children, I illustrate the affective entailments of life-building in post-Apartheid South Africa